Principal Leadership and Teacher Performance: Motivation and Coaching-Based Academic Supervision - Muhammad Zamzami; Agus Wahyudin (Universitas Negeri Semarang, 2026)
This study examines the effect of principal leadership on teacher performance, with teacher work motivation as a mediating variable and coaching-based academic supervision as a moderating variable. A quantitative research design was employed involving 220 public elementary school teachers in Sirampog District, Brebes Regency, Indonesia. Data were collected using structured questionnaires and analyzed using multiple regression, path analysis, Sobel test, and moderated regression analysis. The results indicate that principal leadership has a significant positive effect on teacher performance. Teacher work motivation also significantly influences teacher performance and partially mediates the relationship between principal leadership and teacher performance. Coaching-based academic supervision has a direct positive effect on teacher performance; however, it does not moderate the relationship between principal leadership and teacher performance. The model explains 57.2% of the variance in teacher performance. These findings highlight the importance of effective school leadership and teacher motivation in improving teacher performance, while positioning coaching-based academic supervision as a supportive professional development mechanism rather than a moderating factor. The study contributes to leadership and supervision literature in primary education and provides practical implications for school management.